2021
DOI: 10.1177/1120672121997288
|View full text |Cite
|
Sign up to set email alerts
|

Association of metformin and development of dry age-related macular degeneration in a U.S. insurance claims database

Abstract: Purpose: To assess whether metformin is associated with dry age-related macular degeneration (dAMD) development. Methods: In this retrospective cohort study, patients enrolled in a nationwide U.S. medical insurance claims database from 2002 to 2016 were included if they had diabetes mellitus, were ⩾55 years old, and were enrolled for ⩾2 years without a prior AMD diagnosis. The primary exposure was metformin use analyzed as either active or prior use or cumulative metformin dosage over the study period. A time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(48 citation statements)
references
References 32 publications
0
47
1
Order By: Relevance
“…Some studies reported metformin use to be associated with reduced odds of prevalent [20] or incident AMD [21,61,62], yet others could not confirm a relationship. [51,63] Blitzer et al described the largest benefit of metformin at a low to moderate dosage, indicating a U-shaped dose-response and hypothesized that a high dose may have been indicated in patients with poorly controlled diabetes who hence may benefit less from metformin use. Subsequently, a recent meta-analysis on retrospective data suggested a trend of reduced risk for AMD in patients using metformin without reaching statistical significance, underscoring the scarcity of data and highlighting the need for further prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported metformin use to be associated with reduced odds of prevalent [20] or incident AMD [21,61,62], yet others could not confirm a relationship. [51,63] Blitzer et al described the largest benefit of metformin at a low to moderate dosage, indicating a U-shaped dose-response and hypothesized that a high dose may have been indicated in patients with poorly controlled diabetes who hence may benefit less from metformin use. Subsequently, a recent meta-analysis on retrospective data suggested a trend of reduced risk for AMD in patients using metformin without reaching statistical significance, underscoring the scarcity of data and highlighting the need for further prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Data from retrospective studies are mixed but overall promising. [15][16][17][18]50,51 A large case-control study by our group revealed that metformin use was associated with reduced odds of developing age-related macular degeneration in a dose-dependent manner (OR, 0.93; 95% CI = 0.91-0.95), with low to moderate doses showing the greatest potential benefit. 312,404 patients with newly diagnosed AMD and 313,376 control patients matched on the following criteria: age, anemia, HTN, geography US region, and Charlson comorbidity index (CCI) score (0, 1, 2, or 3+) were identified from the IBM MarketScan Commercial and Medicare Supplemental Databases.…”
Section: Clinical Trialsmentioning
confidence: 98%
“…Even when categorizing patients based on treatment duration, metformin use did not demonstrate a protective effect (>300 days metformin use adjusted OR 0.93;95% CI = 0.68-1.26). 50 A recent retrospective cohort study by Eton et al 51 found that metformin was not protective against the development of dry AMD (dAMD). The authors queried a national US medical insurance claims database between January 2002 and December 2016 to identify an initial cohort of 1,007,226 diabetic patients 55 or older with no previous diagnosis of AMD, no history of DR or treatment for DR, and no other underlying retinal diseases.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Eight retrospective studies have analyzed the association of metformin use with AMD, of which one was a crosssectional study [39], four were cohort studies [40][41][42][43], two were case-control studies [44,45], and one was a nested case-control study [46]. Five studies exclusively determined the association between metformin use and the risk of developing AMD in diabetic patients [39][40][41][42][43], whereas three studies included broader patient groups according to their cohort definition [44][45][46]. One study examined the association of metformin use with dry AMD only [43], while the remaining studies considered all forms of AMD or did not further specify.…”
Section: Effects Of Metformin Use On Amd In Retrospective Clinical Tr...mentioning
confidence: 99%
“…Five studies exclusively determined the association between metformin use and the risk of developing AMD in diabetic patients [39][40][41][42][43], whereas three studies included broader patient groups according to their cohort definition [44][45][46]. One study examined the association of metformin use with dry AMD only [43], while the remaining studies considered all forms of AMD or did not further specify. All other antidiabetic drugs studied showed no association.…”
Section: Effects Of Metformin Use On Amd In Retrospective Clinical Tr...mentioning
confidence: 99%